Penggunaan media kartu bergambar untuk meningkatkan kemampuan membaca awal siswa slow learner - Rahma Widyana; Nurani Sinta Dewi (Jurnal Psikologi Ulayat, 2021)
This study determines the use of pictorial media to improve the initial reading ability of slow learners. The research hypothesizes that a significant increase in reading abilities will occur after receiving the pictorial cards as an intervention’s media. This study applies a pretest-posttest single group design. Wilcoxon’s test analysis showed that there were differences in initial reading ability scores before and after the intervention. The reading ability scores after using the pictorial card media were higher than before the intervention. Therefore, the pictorial media was able to improve the initial reading ability of slow learners based on this study’s samples of elementary students with poor reading skills.